Cantharidin Induces Apoptosis and Promotes Differentiation of AML Cells Through Nuclear Receptor Nur77-Mediated Signaling Pathway - Yu, Zanyang; Li, Li; Wang, Chengqiang; He, Hui; Liu, Gen; Ma, Haoyue; Pang, Lei; Jiang, Mingdong; Lu, Qianwei; Li, Pan; Qi, Hongyi (Frontiers in Pharmacology, 2020)
Background: Acute myeloid leukemia (AML) is a hematopoietic malignancy characterized by uncontrolled proliferation and accumulation of myeloblasts in the bone marrow (BM), blood, and other organs. The nuclear receptors Nur77 is a common feature in leukemic blasts and has emerged as a key therapeutic target for AML. Cantharidin (CTD), a main medicinal component of Mylabris (blister beetle), exerts an anticancer effect in multiple types of cancer cells. Purpose: This study aims to characterize the anti-AML activity of CTD in vitro and in vivo and explore the potential role of Nur77 signaling pathway. Study Design/Methods: The inhibition of CTD on cell viability, proliferation and colony formation was performed in different AML cells. Induction of apoptosis and promotion of differentiation by CTD were further determined. Then, the potential role of Nur77 signaling pathway was assessed. Finally, anti-AML activity was evaluated in NOD/SCID mice. Results: In our study, CTD exhibited potent inhibition on cell viability and colony formation ability of AML cells. Moreover, CTD significantly induced the apoptosis, which was partially reversed by Z-VAD-FMK. Meanwhile, CTD promoted the cleavage of caspase 8, 3 and PARP in HL-60 cells. Furthermore, CTD obviously suppressed the proliferation and induced the cell cycle arrest of HL-60 cells at G2/M phase. Meanwhile, CTD effectively promoted the differentiation of HL-60 cells. Notably, CTD transiently induced the expression of Nur77 protein. Interestingly, CTD promoted Nur77 translocation from the nucleus to mitochondria and enhanced the interaction between Nur77 and Bcl-2, resulting in the exposure of the BH3 domain of Bcl-2, which is critical for the conversion of Bcl-2 from an antiapoptotic to a proapoptotic protein. Importantly, silencing of Nur77 attenuated CTD-induced apoptosis, reversed CTD-mediated cell cycle arrest and differentiation of HL-60 cells. Additionally, CTD also exhibited an antileukemic effect in NOD/SCID mice with the injection of HL-60 cells into the tail vein. Conclusions: Our studies suggest that Nur77-mediated signaling pathway may play a critical role in the induction of apoptosis and promotion of differentiation by CTD on AML cells.